Bioactivity-guided synthesis of gramine derivatives as new MT1 and 5-HT1A receptors agonists. Issue 6 (3rd June 2017) - Yin, Xiu-Juan; Huang, Xiao-Yan; Ma, Yun-Bao; Geng, Chang-An; Li, Tian-Ze; Chen, Xing-Long; Yang, Tong-Hua; Zhou, Jun; Zhang, Xue-Mei; Chen, Ji-Jun
Abstract: Twenty-four gramine derivatives were synthesized and evaluated on MT1 and 5-HT1A receptors in vitro . Among them, seven derivatives (7, 8, 16, 19, 20, 21, and24) exhibited higher agonisting activities on MT1 or 5-HT1A receptors. Compared with gramine, derivatives7, 8, 16, 19, 20, 21, and24 displayed 1.6–3.5-fold increase in agonistic rates on 5-HT1A receptor. Particularly, derivatives7, 19, and21 exhibited significant agonistic activities on MT1 and 5-HT1A receptors with EC50 values of 0.51, 0.39, 0.50 mΜ and 0.28, 0.46, 0.23 mΜ, respectively. The preliminary structure–activity relationships of gramine derivatives were summarized for further investigation on MT1 and 5-HT1A receptors as new potential agonists. Abstract :